The Role of Dominant Follicular Diameter and LH in Predicting Ovulation in Cycle with Clomiphene Citrate - Budi Wiweko (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To improve diagnostic method to predict ovulation in cycle with clomiphene citrate. Method: This diagnostic research was done in RSUPN Dr. Cipto Mangunkusumo between January 2011 - October 2011 with 31 women who taking CC 50 mg/day and 30 women with normal cycle. Result: Affecting with ovulation in the two groups, it was found that in groups with CC, the follicle diameter is 24.33 ± 3.87 mm with LH 14.21 ± 7.95 IU/l, meanwhile in normal group, follicular diameter is 17.62 ± 3.45 mm with LH 14.42 ± 5.91 IU/l. Cut-off point for follicular diameter simultaneously with ovulation determined by ROC curve was found in 24.33mm (AUC 0.67, sensitivity 0.64, specificity 0.56), meanwhile the cut-off for LH is 14.40 IU/l (AUC 0.61, sensitivity 0.57, specificity 0.43). Conclusion: In group with CC, ovulation occurred in bigger follicular diameter than normal cycle, while LH does not different significantly. [Indones J Obstet Gynecol 2011; 35-3: 128-9] Keywords: clomiphene citrate, follicular diameter, luteinizing hormone